Immunophenotypic Characterization of Human Bone Marrow Mast Cells. A Flow Cytometric Study of Normal and Pathological Bone Marrow Samples - Luis Escribano; Alberto Orfao; Jesús Villarrubia; Beatriz Díaz-Agustín; Carlos Cerveró; Agustín Rios; José L. Velasco; Juana Ciudad; José L. Navarro; Jesús F. San Miguel (Analytical Cellular Pathology)
The goal of the present paper was to define the immunophenotype of bone marrow mast cells (BMMC) from healthy controls and patients with hematologic malignancies (HM) based on the use of multiple stainings with monoclonal antibodies analyzed by flow cytometry. Our results show that BMMC from both groups of individuals display a similar but heterogenous immunophenotype. The overall numbers of BMMC are higher in the HM group of individuals (p = 0.08). Three patterns of antigen expression were detected: (1) markers constantly positive in all cases analyzed (CD9, CD29, CD33, CD43, CD44, CD49d, CD49e, CD51, CD71, CD117, and FcεRI), (2) antigens that were constantly negative (CD1a, CD2, CD3, CD5, CD6, CD11a, CD14, CD15, CD16, CD19, CD20, CD21, CD23, CD25, CD30, CD34, CD38, CD41a, CD42b, CD65, CD66b, HLA-DR, and CD138), and (3) markers that were positive in a variable proportion of cases – CD11b (50%), CD11c (77%), CD13 (40%), CD18 (20%), CD22 (68%), CD35 (27%), CD40 (67%), CD54 (88%) and CD61 (40%). In addition, BMMC from all cases explored were CD45+, and this antigen was expressed at an intensity similar to that of mature granulocytes.